A generic algorithmic protocol approaches to improve network life time and energy efficient using combined genetic algorithm with simulated annealing in MANET. Issue 1 (8th July 2019) - A.Y., Prasad; Rayanki, Balakrishna
Abstract : Purpose: In the present networking scenarios, MANETs mainly focus on reducing the consumed power of battery-operated devices. The transmission of huge data in MANETs is responsible for greater energy usage, thereby affecting the parameter metrics network performance, throughput, packet overhead, energy consumption in addition to end-to-end delay. The effective parameter metric measures are implemented and made to enhance the network lifetime and energy efficiency. The transmission of data for at any node should be more efficient and also the battery of sensor node battery usage should be proficiently applied to increase the network lifetime. The paper aims to discuss these issues. Design/methodology/approach: In this research work for the MANETs, the improvement of energy-efficient algorithms in MANETs is necessary. The main aim of this research is to develop an efficient and accurate routing protocol for MANET that consumes less energy, with an increased network lifetime. Findings: In this paper, the author has made an attempt to improve the genetic algorithm with simulated annealing (GASA) for MANET to minimize the energy consumption of 0.851 percent and to enhance the network lifetime of 61.35 percent. Originality/value: In this paper, the author has made an attempt to improve the GASA for MANET to minimize the energy consumption of 0.851 percent and to enhance the network lifetime of 61.35 percent.